106 Daily firearm carriage and interpersonal violence patterns among a high-risk urban emergency department (ED) sample of youth and young adults. (5th May 2020) - Carter, Patrick; Walton, Maureen; Myers, Matt; Resnicow, Ken; Zimmerman, Marc; Goldstick, Jason; Cunningham, Rebecca
Abstract : Statement-of-Purpose: Firearm violence is a leading cause of U.S. mortality. Intensive longitudinal daily data studies [ILDDS] have not examined firearm carriage or same-day/next-day predictors of carriage or violent conflict. Such data are necessary to inform violence interventions. Methods/Approach: ED youth/young adults (age=16–29) screening positive for substance misuse, firearm possession, and smartphone ownership were enrolled in a 30-day ILDDS. Daily assessment included 31-items about firearm carriage, violence, substance use, anger, anxiety/stress, and impulsivity. Separate conditional logistic regression models examined within- and next-day lagged associations with firearm carriage and violent conflict. Results: Across 30-days, 51% (n=27) of participants (n=53; M-age=24; 42%-male; 68%-Black; 87%-handgun possession) carried firearms, averaging 7 carriage-days/person. Carriage did not vary by day, week, day-of-week, or weekday/weekend. Firearms were carried 17% (180-of-1046) of days, with protection (97%) the primary reason-for-carriage and perceived low-risk (75%) the primary reason-for-not-carrying; 19% of participants disposed of their firearms. Examining between-person associations, no baseline differences were identified for participants carrying and not carrying firearms. Examining within-day factors, using illicit drugs (OR=7.5) and spending time in high-risk locations (OR=3.5) were associated with same-day carriage. No same-day associations were identified for other daily variables and carriage. Across 30-days, 26% of participants engaged in violent conflict (n=20 conflict-days; 63%-partner/27%-non-partner, 25%-firearm threats/use). Examining within-day, higher anger (OR=1.48), impulsivity (OR=1.28), stress/anxiety (OR=1.35), and riskier firearm behaviors (e.g., carriage drunk/high; OR=6.46) were associated with same-day conflict. Higher anger (OR=9.63) and lower self-efficacy for avoiding fights (OR=1.42) were associated with next-day conflict. Conclusions: Among high-risk youth, daily firearm carriage/violence rates were high. Results highlight carriage patterns and foci for interventions, including risky firearm behaviors, illicit-drug use, anxiety/stress, impulse control, anger management, and violence avoidance/refusal skills. Significance/Contributions: This is the first ILDDS examining firearm carriage/violence and identifies key data for future public health efforts addressing firearm violence.